Anti-crack waterproof mortar and production method thereof

By using cement base materials, fine aggregates, polymer modifiers, fiber reinforced materials, waterproof additives and composite admixtures in the mortar, combined with mechanical grinding and ultrasonic treatment technology, the problems of poor crack resistance and poor waterproofing performance of traditional mortars are solved, significantly improving the crack resistance and waterproofing performance of mortars and providing higher quality assurance for construction projects.

CN119735406APending Publication Date: 2025-04-01CHANGSHA CAIDING NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411932438.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

In actual applications, traditional mortar has poor crack resistance and poor waterproofing effects, which leads to cracks that are prone to cracks under the influence of increased service life and environmental factors, which leads to problems such as moisture penetration, wall leakage and mold, shortening the service life of the building and increasing maintenance costs.

Method used

A crack-resistant waterproof mortar is adopted, and its components include cement base material, fine aggregate, polymer modifier, fiber reinforced material, waterproof additive and composite admixture. Nanofibers are prepared by mechanical grinding, and combined with ultrasonic treatment, the amount and method of adding hydrophobic materials are optimized to form hydrophobic channels or waterproof layers to enhance the crack-resistant and waterproof properties of the mortar.

Benefits of technology

It significantly improves the crack resistance and waterproof performance of the mortar, avoids the inherent defects of traditional mortar, provides higher quality assurance for construction projects, extends the service life of the building and reduces maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of building material preparation, in particular to anti-crack waterproof mortar and a production method thereof. According to the technical scheme, the concrete comprises the following raw materials: 20-30 parts of a cement-based material, 35-45 parts of fine aggregate, 10-15 parts of a polymer modifier, 0.3-0.8 part of a fiber-reinforced material, 3-6 parts of a waterproof additive and 1-3 parts of a composite additive. The fiber reinforced material is prepared by adopting a mechanical grinding method; the preparation method comprises the following steps: putting the fiber reinforced material into a ball mill; the grinding time and the size and number of grinding balls are controlled; and the ground nano-fibers are put into use after being observed. The raw materials are carefully screened and optimally combined, and a unique production process is combined, so that the anti-cracking and waterproof properties of the mortar are remarkably improved, the inherent defects of the traditional mortar are effectively overcome, and a solid guarantee is provided for the quality of constructional engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building material preparation, and in particular to a crack-resistant waterproof mortar and a production method thereof. Background Art

[0002] In modern construction projects, mortar is a key basic material, and its performance is directly related to the durability and safety of building structures. However, traditional mortar has exposed many defects in practical applications, among which poor crack resistance and poor waterproof effect are particularly prominent. With the increase in the service life of buildings and the influence of environmental factors, ordinary mortar is prone to cracks, which not only destroys the aesthetic appearance of the building, but more seriously opens up channels for water penetration, leading to a series of problems such as wall leakage and mold, greatly shortening the service life of the building, increasing maintenance costs and waste of resources. For example, in the rainy season in the south and the freeze-thaw cycle environment in the north, a large number of cracks appear in the mortar layer of the exterior walls of many buildings, rainwater penetrates into the interior of the wall, causing the interior decoration layer to become damp and peel off, affecting the stability of the building structure and the health of the residents. In cold areas in the north, frequent freeze-thaw cycles can cause mortar cracks to expand rapidly, accelerate wall damage, increase maintenance costs and resource consumption, and seriously restrict the sustainable development of the construction industry. Therefore, it is urgent to develop a high-performance crack-resistant and waterproof mortar. Summary of the invention

[0003] The purpose of the present invention is to provide a crack-resistant waterproof mortar and a production method thereof in view of the problems existing in the background technology.

[0004] On the one hand, the present application provides a crack-resistant waterproof mortar, comprising the following component raw materials:

[0005] 20-30 parts of cement base material, 35-45 parts of fine aggregate, 10-15 parts of polymer modifier, 0.3-0.8 parts of fiber reinforcement material, 3-6 parts of waterproof additive, 1-3 parts of composite admixture;

[0006] The fiber-reinforced material is prepared by mechanical grinding;

[0007] The preparation steps are:

[0008] The fiber reinforcement material is put into a ball mill;

[0009] Control grinding time and the size and number of grinding balls;

[0010] The ground nanofibers were observed and put into use.

[0011] Optionally, the anti-cracking and waterproof mortar includes the following raw materials: 25 parts of cement base material, 30 parts of fine aggregate, 12.5 parts of polymer modifier, 0.5 parts of fiber reinforcement material, 4.5 parts of waterproof additive, and 2 parts of composite admixture;

[0012] In the preparation of fiber reinforced materials, the grinding balls are 3-5 mm steel balls, the ball-to-material ratio is 1:2-1:3, and the grinding time is 30-60 minutes.

[0013] Optionally, the anti-cracking and waterproof mortar includes the following component raw materials: 20 parts of cement base material, 35 parts of fine aggregate, 10 parts of polymer modifier, 0.3 parts of fiber reinforcement material, 3 parts of waterproof additive, and 1 part of composite admixture.

[0014] Optionally, the anti-cracking and waterproof mortar includes the following raw materials: 30 parts of cement base material, 45 parts of fine aggregate, 15 parts of polymer modifier, 0.8 parts of fiber reinforcement material, 6 parts of waterproof additive, and 3 parts of composite admixture.

[0015] Optionally, the cement base material is ordinary Portland cement with a strength grade of 42.5;

[0016] Fine aggregates are medium sand and ultrafine mineral powder with a particle size of 0.15-1.18, and the ratio of medium sand to ultrafine mineral powder is 3:0.2;

[0017] The polymer modifier is a mixture of styrene acrylic emulsion and acrylic emulsion, with a ratio of 1:1.2;

[0018] The fiber reinforcement material is either polypropylene fiber or glass fiber;

[0019] The waterproof additive is any one of an organic silicon waterproof agent or a fatty acid waterproof agent;

[0020] The composite admixture includes a water reducing agent, an expansive agent and an air entraining agent. The water reducing agent is used to reduce the water used in the mortar to ensure the fluidity and strength of the mortar; the expansive agent is used to expand during the hardening process of the mortar to enhance the crack resistance; the air entraining agent is used to introduce tiny closed bubbles into the mortar to enhance the freeze-thaw resistance of the mortar.

[0021] On the other hand, the present application provides a method for producing crack-resistant waterproof mortar, comprising the following preparation steps:

[0022] Step 1: Pre-process the raw materials of the components to be processed in the material to obtain the substrate used for preparation;

[0023] Step 2: Use a high-precision electronic scale to accurately weigh the cement base, fine aggregate, polymer modifier, waterproof additive and composite admixture raw materials in sequence, put the cement base and fine aggregate into the forced mixer first, start the mixer for dry mixing, and continue mixing for 3-5 minutes until a uniform dry mix is ​​formed;

[0024] Step 3: Slowly add the polymer modifier, waterproof additive and composite admixture to the dry mix being stirred, and adjust the mixer speed to 40-60 rpm. Continue stirring for 4-6 minutes to ensure that the various liquid materials and the dry mix are fully mixed and evenly formed to form a stable mixing system.

[0025] Step 4: Slowly add the dispersed fiber-reinforced material into the mixer, increase the stirring speed to 50-70 rpm, and continue stirring for 6-8 minutes until the fibers are evenly distributed in the mortar to obtain a crack-resistant and waterproof mortar product.

[0026] Optionally, the pretreatment of the component raw materials in step 1 includes screening of cement base and fine aggregate, the mesh number of the cement base screening is 100-120 mesh, and the mesh number of the fine aggregate screening is 60-80 mesh. This step is used to remove impurity particles and large particles in the cement base and fine aggregate to ensure the particle size uniformity and purity of the raw materials.

[0027] Optionally, the fiber-reinforced material further comprises an ultrasonic treatment method for its preparation:

[0028] Specifically, the processing steps include: placing the fiber in a solution containing a dispersant, and then inserting an ultrasonic probe into the solution; setting the frequency of the ultrasound to 20-40kHz, the power to 100-500W, and the processing time to 10-30 minutes; under the action of ultrasound, the tiny bubbles in the solution will collapse near the fiber surface, and the energy generated will disperse the fiber, thereby enhancing the dispersion of the fiber.

[0029] Compared with the prior art, the present invention has the following beneficial technical effects:

[0030] The present invention can make the fiber material more evenly distributed in the mortar by modifying the fiber material, realize a more effective anti-cracking network, avoid the agglomeration problem of traditional fibers in the mortar, and thus improve the crack resistance of the mortar;

[0031] The present invention optimizes the hydrophobic material to form a hydrophobic channel inside the mortar or a waterproof layer on the surface to prevent the intrusion of water, and at the same time optimizes the optimal addition amount and addition method of the hydrophobic material to ensure that the waterproof performance is improved to the greatest extent without affecting other properties of the mortar.

[0032] Furthermore, by using ultra-fine mineral powder in the mortar material to fill the gaps between cement particles, the structure of the mortar is more compact and the waterproofness is improved;

[0033] In summary, the present invention carefully screens and optimizes the combination of raw materials, combined with a unique production process, which significantly improves the crack resistance and waterproof performance of the mortar, effectively overcomes the inherent defects of traditional mortar, and provides a solid guarantee for the quality of construction projects. DETAILED DESCRIPTION

[0034] The technical solution of the present disclosure will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present disclosure, rather than all of the embodiments.

[0035] The components of the embodiments of the present disclosure generally described and shown herein may be arranged and designed in a variety of different configurations. Therefore, the following detailed description of the embodiments is not intended to limit the scope of the claimed disclosure, but merely represents selected embodiments of the disclosure.

[0036] Based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present disclosure.

[0037] In the description of the present disclosure, it should be noted that the terms "center", "up", "down", "left", "right", "vertical", "horizontal", "inside", "outside", etc., indicating directions or positional relationships, are only for the convenience of describing the present disclosure and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific direction, be constructed and operated in a specific direction, and therefore should not be understood as a limitation on the present disclosure.

[0038] In the description of the present disclosure, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present disclosure can be understood according to specific circumstances.

[0039] Example 1

[0040] The present invention provides an anti-cracking and waterproof mortar, comprising the following component raw materials:

[0041] 25 parts of cement base, 30 parts of fine aggregate, 12.5 parts of polymer modifier, 0.5 parts of fiber reinforcement, 4.5 parts of waterproof additive, 2 parts of composite admixture;

[0042] The cement base material is ordinary Portland cement with a strength grade of 42.5;

[0043] Fine aggregates are medium sand with a particle size of 1.1 and ultrafine mineral powder, and the ratio of medium sand to ultrafine mineral powder is 3:0.2;

[0044] The polymer modifier is a mixture of styrene acrylic emulsion and acrylic emulsion, with a ratio of 1:1.2;

[0045] The fiber reinforcement material uses polypropylene fiber;

[0046] The waterproof additive adopts silicone waterproofing agent;

[0047] Composite admixtures include water reducing agent, expansion agent and air entraining agent;

[0048] The water reducing agent is used to reduce the water used in the mortar to ensure the fluidity and strength of the mortar;

[0049] The expansion agent is used to generate expansion during the mortar hardening process to enhance crack resistance;

[0050] The air entraining agent is used to introduce tiny closed bubbles into the mortar to enhance the freeze-thaw resistance of the mortar.

[0051] The fiber-reinforced material is prepared by mechanical grinding;

[0052] The preparation steps are:

[0053] The fiber reinforcement material is put into a ball mill;

[0054] Control the grinding time and the size and number of grinding balls; use 5 mm steel balls for grinding balls, the ball-to-material ratio is 1:2.5, and the grinding time is 55 minutes;

[0055] The ground nanofibers were observed and put into use.

[0056] This embodiment also provides a production method for anti-cracking and waterproof mortar, including the following preparation steps:

[0057] Step 1: pre-processing the component raw materials to be processed in the material to obtain the substrate used for preparation; the pre-processing of the component raw materials includes screening of cement base material and fine aggregate, the mesh number of the cement base material screening is 120 meshes, and the mesh number of the fine aggregate screening is 80 meshes. This step is used to remove impurity particles and large particles in the cement base material and fine aggregate to ensure the particle size uniformity and purity of the raw materials;

[0058] Step 2: Use a high-precision electronic scale to accurately weigh the cement base, fine aggregate, polymer modifier, waterproof additive and composite admixture raw materials in sequence, put the cement base and fine aggregate into a forced mixer first, start the mixer for dry mixing, and continue mixing for 4 minutes until a uniform dry mix is ​​formed;

[0059] Step 3: Slowly add the polymer modifier, waterproof additive and composite admixture to the dry mix being stirred, and adjust the mixer speed to 55 rpm. Continue stirring for 6 minutes to ensure that the various liquid materials and the dry mix are fully mixed and evenly formed to form a stable mixing system.

[0060] Step 4: Slowly add the dispersed fiber-reinforced material into the mixer, increase the stirring speed to 55 rpm, and continue stirring for 7 minutes until the fibers are evenly distributed in the mortar to obtain a crack-resistant and waterproof mortar product.

[0061] Example 2

[0062] Based on Example 1, an anti-cracking mortar is also proposed, comprising the following component raw materials:

[0063] 20 parts of cement base material, 35 parts of fine aggregate, 10 parts of polymer modifier, 0.3 parts of fiber reinforcement material, 3 parts of waterproof additive, 1 part of composite admixture;

[0064] The cement base material is ordinary Portland cement with a strength grade of 42.5;

[0065] Fine aggregates are medium sand with a particle size of 1.1 and ultrafine mineral powder, and the ratio of medium sand to ultrafine mineral powder is 3:0.2;

[0066] The polymer modifier is a mixture of styrene acrylic emulsion and acrylic emulsion, with a ratio of 1:1.2;

[0067] The fiber reinforcement material uses polypropylene fiber;

[0068] The waterproof additive adopts silicone waterproofing agent;

[0069] Composite admixtures include water reducing agent, expansion agent and air entraining agent;

[0070] The water reducing agent is used to reduce the water used in the mortar to ensure the fluidity and strength of the mortar;

[0071] The expansion agent is used to generate expansion during the mortar hardening process to enhance crack resistance;

[0072] The air entraining agent is used to introduce tiny closed bubbles into the mortar to enhance the freeze-thaw resistance of the mortar.

[0073] The fiber-reinforced material is prepared by mechanical grinding;

[0074] The preparation steps are:

[0075] The fiber reinforcement material is put into a ball mill;

[0076] Control the grinding time and the size and number of grinding balls; use 5 mm steel balls for grinding balls, the ball-to-material ratio is 1:2.5, and the grinding time is 55 minutes;

[0077] The ground nanofibers were observed and put into use.

[0078] This embodiment also provides a production method for anti-cracking and waterproof mortar, including the following preparation steps:

[0079] Step 1: pre-processing the component raw materials to be processed in the material to obtain the substrate used for preparation; the pre-processing of the component raw materials includes screening of cement base material and fine aggregate, the mesh number of the cement base material screening is 120 meshes, and the mesh number of the fine aggregate screening is 80 meshes. This step is used to remove impurity particles and large particles in the cement base material and fine aggregate to ensure the particle size uniformity and purity of the raw materials;

[0080] Step 2: Use a high-precision electronic scale to accurately weigh the cement base, fine aggregate, polymer modifier, waterproof additive and composite admixture raw materials in sequence, put the cement base and fine aggregate into a forced mixer first, start the mixer for dry mixing, and continue mixing for 4 minutes until a uniform dry mix is ​​formed;

[0081] Step 3: Slowly add the polymer modifier, waterproof additive and composite admixture to the dry mix being stirred, and adjust the mixer speed to 55 rpm. Continue stirring for 6 minutes to ensure that the various liquid materials and the dry mix are fully mixed and evenly formed to form a stable mixing system.

[0082] Step 4: Slowly add the dispersed fiber-reinforced material into the mixer, increase the stirring speed to 55 rpm, and continue stirring for 7 minutes until the fibers are evenly distributed in the mortar to obtain a crack-resistant and waterproof mortar product.

[0083] Example 3

[0084] Based on Example 1, another anti-cracking mortar is proposed, comprising the following component raw materials:

[0085] 30 parts of cement base, 45 parts of fine aggregate, 15 parts of polymer modifier, 0.8 parts of fiber reinforcement, 6 parts of waterproof additive, 3 parts of composite admixture;

[0086] The cement base material is ordinary Portland cement with a strength grade of 42.5;

[0087] Fine aggregates are medium sand with a particle size of 1.1 and ultrafine mineral powder, and the ratio of medium sand to ultrafine mineral powder is 3:0.2;

[0088] The polymer modifier is a mixture of styrene acrylic emulsion and acrylic emulsion, with a ratio of 1:1.2;

[0089] The fiber reinforcement material uses polypropylene fiber;

[0090] The waterproof additive adopts silicone waterproofing agent;

[0091] Composite admixtures include water reducing agent, expansion agent and air entraining agent;

[0092] The water reducing agent is used to reduce the water used in the mortar to ensure the fluidity and strength of the mortar;

[0093] The expansion agent is used to generate expansion during the mortar hardening process to enhance crack resistance;

[0094] The air entraining agent is used to introduce tiny closed bubbles into the mortar to enhance the freeze-thaw resistance of the mortar.

[0095] The fiber-reinforced material is prepared by mechanical grinding;

[0096] The preparation steps are:

[0097] Fiber reinforced materials also include ultrasonic treatment for their preparation:

[0098] The specific processing steps include: placing the fiber in a solution containing a dispersant, and then inserting an ultrasonic probe into the solution; setting the frequency of the ultrasonic wave to 35kHz, the power to 400W, and the processing time to 25 minutes; under the action of the ultrasonic wave, the tiny bubbles in the solution will collapse near the fiber surface, and the energy generated will disperse the fiber, thereby enhancing the dispersion of the fiber;

[0099] This embodiment also provides a production method for anti-cracking and waterproof mortar, including the following preparation steps:

[0100] Step 1: pre-processing the component raw materials to be processed in the material to obtain the substrate used for preparation; the pre-processing of the component raw materials includes screening of cement base material and fine aggregate, the mesh number of the cement base material screening is 120 meshes, and the mesh number of the fine aggregate screening is 80 meshes. This step is used to remove impurity particles and large particles in the cement base material and fine aggregate to ensure the particle size uniformity and purity of the raw materials;

[0101] Step 2: Use a high-precision electronic scale to accurately weigh the cement base, fine aggregate, polymer modifier, waterproof additive and composite admixture raw materials in sequence, put the cement base and fine aggregate into a forced mixer first, start the mixer for dry mixing, and continue mixing for 4 minutes until a uniform dry mix is ​​formed;

[0102] Step 3: Slowly add the polymer modifier, waterproof additive and composite admixture to the dry mix being stirred, and adjust the mixer speed to 55 rpm. Continue stirring for 6 minutes to ensure that the various liquid materials and the dry mix are fully mixed and evenly formed to form a stable mixing system.

[0103] Step 4: Slowly add the dispersed fiber-reinforced material into the mixer, increase the stirring speed to 55 rpm, and continue stirring for 7 minutes until the fibers are evenly distributed in the mortar to obtain a crack-resistant and waterproof mortar product.

[0104] The compressive strength, flexural strength, crack resistance, waterproof performance, bonding strength and freeze-thaw resistance of the mortar prepared by the preparation method of Example 1, Example 2 and Example 3 were tested according to relevant standards and industry specifications, wherein the freeze-thaw resistance was recorded within 50 freeze-thaw cycles, and whether there was obvious breakage, peeling and cracking on the surface of the mortar was tested, which was specifically reflected in: no damage, slight damage, moderate damage and severe damage;

[0105] The following data is obtained:

[0106]

[0107]

[0108] Combined with the above data table, it can be seen that the mortar prepared in Example 1 in this scheme has the best performance and is the optimal embodiment.

[0109] The above specific embodiments are only several optional embodiments of the present invention. Based on the technical solutions of the present invention and the relevant inspirations of the above embodiments, those skilled in the art can make various alternative improvements and combinations to the above specific embodiments.

Claims

1. A crack-resistant waterproof mortar, characterized in that: Including the following raw materials: 20-30 parts of cement base material, 35-45 parts of fine aggregate, 10-15 parts of polymer modifier, 0.3-0.8 parts of fiber reinforcement material, 3-6 parts of waterproof additive, 1-3 parts of composite admixture; The fiber-reinforced material is prepared by mechanical grinding; The preparation steps are: The fiber reinforcement material is put into a ball mill; Control grinding time and the size and number of grinding balls; The ground nanofibers were observed and put into use.

2. The anti-cracking and waterproof mortar according to claim 1, characterized in that: The anti-cracking waterproof mortar comprises the following raw materials: 25 parts of cement base material, 30 parts of fine aggregate, 12.5 parts of polymer modifier, 0.5 parts of fiber reinforcement material, 4.5 parts of waterproof additive, and 2 parts of composite admixture; In the preparation of fiber reinforced materials, the grinding balls are 3-5 mm steel balls, the ball-to-material ratio is 1:2-1:3, and the grinding time is 30-60 minutes.

3. The anti-cracking and waterproof mortar according to claim 1, characterized in that: The anti-cracking waterproof mortar includes the following raw materials: 20 parts of cement base material, 35 parts of fine aggregate, 10 parts of polymer modifier, 0.3 parts of fiber reinforcement material, 3 parts of waterproof additive, and 1 part of composite admixture.

4. The anti-cracking and waterproof mortar according to claim 1, characterized in that: The anti-cracking waterproof mortar comprises the following raw materials: 30 parts of cement base material, 45 parts of fine aggregate, 15 parts of polymer modifier, 0.8 parts of fiber reinforcement material, 6 parts of waterproof additive, and 3 parts of composite admixture.

5. The anti-cracking and waterproof mortar according to claim 4, characterized in that: The cement base material is ordinary Portland cement with a strength grade of 42.5; Fine aggregates are medium sand and ultrafine mineral powder with a particle size of 0.15-1.18, and the ratio of medium sand to ultrafine mineral powder is 3:0.2; The polymer modifier is a mixture of styrene acrylic emulsion and acrylic emulsion, with the ratio of the two being 1:1.2; The fiber reinforcement material is either polypropylene fiber or glass fiber; The waterproof additive is any one of an organic silicon waterproof agent or a fatty acid waterproof agent; The composite admixture includes a water reducing agent, an expansive agent and an air entraining agent. The water reducing agent is used to reduce the water used in the mortar to ensure the fluidity and strength of the mortar; the expansive agent is used to expand during the hardening process of the mortar to enhance the crack resistance; the air entraining agent is used to introduce tiny closed bubbles into the mortar to enhance the freeze-thaw resistance of the mortar.

6. A method for producing the anti-cracking and waterproof mortar according to any one of claims 1 to 5, characterized in that: The method comprises the following preparation steps: Step 1: pre-processing the raw materials of the components to be processed in the material to obtain the substrate used for preparation; Step 2: Use a high-precision electronic scale to accurately weigh the cement base, fine aggregate, polymer modifier, waterproof additive and composite admixture raw materials in sequence, put the cement base and fine aggregate into the forced mixer first, start the mixer for dry mixing, and continue mixing for 3-5 minutes until a uniform dry mix is ​​formed; Step 3: Slowly add the polymer modifier, waterproof additive and composite admixture to the dry mix being stirred, and adjust the mixer speed to 40-60 rpm. Continue stirring for 4-6 minutes to ensure that the various liquid materials and the dry mix are fully mixed and evenly formed to form a stable mixing system. Step 4: Slowly add the dispersed fiber-reinforced material into the mixer, increase the stirring speed to 50-70 rpm, and continue stirring for 6-8 minutes until the fibers are evenly distributed in the mortar to obtain a crack-resistant and waterproof mortar product.

7. The method for producing crack-resistant waterproof mortar according to claim 6, characterized in that: The pretreatment of the component raw materials in step 1 includes screening of cement base material and fine aggregate, the mesh number of the cement base material screening is 100-120 mesh, and the mesh number of the fine aggregate screening is 60-80 mesh. This step is used to remove impurity particles and large particles in the cement base material and fine aggregate to ensure the particle size uniformity and purity of the raw materials.

8. The method for producing crack-resistant waterproof mortar according to claim 6, characterized in that: The fiber-reinforced material also includes an ultrasonic treatment method for its preparation, which specifically includes the following processing steps: The fiber is placed in a solution containing a dispersant, and an ultrasonic probe is inserted into the solution; Set the ultrasonic frequency to 20-40kHz, the power to 100-500W, and the treatment time to 10-30 minutes; Under the action of ultrasound, tiny bubbles in the solution collapse near the fiber surface, and the energy generated causes the fibers to disperse.